Herd Behavior and Rational Expectations: A Test of China's Market Using Quantile Regression - Chen, Yi-Chang; Wu, Hung-Che; Huang, Jen-Jsung (International Journal of Economics and Financial Issues, 2017)
This paper aims to examine whether the changes of the rational expectations of a tendency to herd among investors under different market conditions in China's market. We find that herding remains scarce during periods of market tumult. Also, herd behavior is more pronounced under rising market conditions. The results indicate that investors show different levels of rational expectations; in particular, herding strongly exists in irrational expectations. The asymmetric information effect exists in market conditions and the reactions to both fundamentals and non-fundamentals. There is no evidence of herding spillover effect from the US stock market to China's market. In spite of investors facing the financial crisis and external effects simultaneously, they still tend to follow the market consensus. This paper claims that investors' herd behavior may be obviously different due to the effectiveness of regulation, information efficiency and market integrations. Keywords: Rational Expectations, Herd behavior, Asymmetric Information Effect, Spillover Effect JEL Classifications: G14, G11, G02